Desenvolvimento de nanofibras poliméricas por fiação por sopro em solução visando aplicação em engenharia de tecido - Paschoalin, Rafaella Takehara (2017)
Tissue engineering is now essential for medical applications, such as in implants for biomedical devices, artificial organs, healing and skin regeneration. The success of these applications depends on the development of biomaterials, which should be accompanied by the study of biomaterial/cell interactions. In this work, nanostructured polymer mats were developed with a solution blow spinning technique (SBS). Polymers mats were characterized aiming the knowledge of their physicochemical properties as well as the processing effects and their effects in the biological response. Specifically, mats composed of poly(lactic acid) (PLA) fibers and PLA/polyethyleneglycol (PEG) blends were produced in the ratio of PLA/PEG 99:1, 95:5, 90:10 and 80:20 (m/m). PEG dissolution of the PLA/PEG polymer mats was evaluated with phosphate buffered saline (PBS) and cell culture medium. Also, the biodegradation of polymer mats was evaluated by culture in agar, which was performed by inoculating the Staphylococcus aureus bacteria on the fibers. The results of the polymer mats with PBS and cell culture medium demonstrated that after 12 hours of exposure a portion of PEG on the fiber surface was dissolved, probably due to PEG solubility in water, that can be used to adjust the polymeric fibers degradation rates. The biodegradation results allowed observing the degradation in function of the polymer fibers incubation time by means of the action of S. aureus bacteria. Cytotoxicity of mesenchymal stem cells (CTM) seeded on polymer mats were determined by the LDH release medium and MTT (Abbreviation for the dye compound 3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromidefor) assay. The release of LDH into the culture medium and MTT assay demonstrated that the scaffolds are not cytotoxic. The response of immature dendritic cells (iDCs) interaction with polymers mats was analyzed. The results showed that dendritic cells physically interacted and furthermore moved along nanofibers. After contact with biomaterials DCs cells showed the costimulatory molecules levels and MHC class II were similar to the immature DCs control group. DCs retained an immature phenotype, which is characterized by low or absent expression of up regulation of surface marker and cytokines. Thus, PLA fibers and the PLA/PEG blends do not stimulated DCs maturation. PLA nanofibers and PLA/PEG blends are not cytotoxic and do not induce dendritic cell maturation then, they become interesting for tissue engineering application.